Step
*
1
of Lemma
bag-member-bag-diff
1. T : Type
2. eq : EqDecider(T)
3. x : T
4. bs : bag(T)
5. y : Unit
6. bag-diff(eq;bs;{x}) = (inr y ) ∈ (bag(T)?)
7. ∀cs:bag(T). (¬(bs = ({x} + cs) ∈ bag(T)))
8. ∃as:bag(T). (bs = ({x} + as) ∈ bag(T))
⊢ False
BY
{ (ExRepD THEN InstHyp [⌜as⌝] (-3)⋅ THEN Auto) }
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  x  :  T
4.  bs  :  bag(T)
5.  y  :  Unit
6.  bag-diff(eq;bs;\{x\})  =  (inr  y  )
7.  \mforall{}cs:bag(T).  (\mneg{}(bs  =  (\{x\}  +  cs)))
8.  \mexists{}as:bag(T).  (bs  =  (\{x\}  +  as))
\mvdash{}  False
By
Latex:
(ExRepD  THEN  InstHyp  [\mkleeneopen{}as\mkleeneclose{}]  (-3)\mcdot{}  THEN  Auto)
Home
Index